Hubungan Preeklampsia dengan Persalinan Prematur di RS Islam Lumajang Tahun 2024 - Amaliyah, Rizka; Ilmiah , Widia Shofa (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine whether there is a relationship between Preeclampsia and premature birth at Lumajang Regional Hospital. The method used in this study is observational, using a Cross-sectional research design. Where the sampling was done using a sampling technique with a total of 399. And the data used is secondary data, obtained from patient medical records. After the data was collected, the data was then processed and processed using SPSS to see the relationship. The Chi-square hypothesis test was used with a significance level (α = 0.05). Based on this study, a p value of 0.063> α = 0.05 was obtained, which means that there is no significant relationship between Preeclampsia and premature birth. Based on this study, it was concluded that there is no relationship between Preeclampsia and premature birth at Lumajang Regional Hospital in 2024. Health workers are expected to provide promotive efforts to high-risk pregnant women, especially with Preeclampsia, in order to improve healthy lifestyles so that pregnant women become more concerned about their health.